AB0721 The Clinical Characteristics and Associated Factors of Chinese Ankylosing Spondylitis Patients. (15th July 2016) - Zheng, X.; Li, Q.; Tu, L.; Lv, Q.; Yang, M.; Zhang, Y.; Lin, Z.; Liao, Z.; Cao, S.; Wei, Q.; Qi, J.; Yuan, R.; et al.
Abstract : Background: Ankylosing Spondylitis (AS) is the prototype of spondyloarthritis, with inflammatory back pain (IBP) as its most typical clinical characteristic and others including peripheral arthritis, anterior uveitis, dactylitis and so on. Human leucocyte antigen B27 (HLA-B27) status, gender and some other factors have been reported to be related with the disease clinical characteristics. Objectives: We aim to describe the clinical spectrum of Chinese AS patients and investigate the influence of HLA-B27 status, gender and age at disease onset factors on the clinical features. Methods: Chinese AS patients with complete clinical data and fulfilling the 1984 Modified New York criteria are studied. The recorded parameters include age, sex, HLA-B27 status, family history, age at AS onset, symptom at onset, disease pattern and presence of IBP, peripheral arthritis, hip joint involvement, anterior uveitis, dactylitis and enthesitis. Chi-square test and independent samples t-test are applied between groups of categorical and continuous variables respectively, using SPSS version 13.0 software. Results: (1) A total of 1630 Chinese AS patients with a gender ratio of 3.36:1, average age of 27.84±9.07 and age at disease onset of 22.03±7.62 are included.17.2% have positive family history and 18.3% have juvenile onset AS (JoAS). (2) The overall HLA-B27 prevalence is 84.2%. HLA-B27 positive group has a younger age at onset (21.86±7.48 vs 22.92±8.31, p=0.041), higher presence of IBP (86.62% vs 78.35%, p=0.001) and hip joint involvement (53.12% vs 43.25%, p=0.004) than B27 negative group. (3) However, HLA-B27 positivity still shows some differences within different gender cohort. In the male group HLA-B27 positivity only shows higher prevalence of family history and IBP (86.62% vs 78.35%, p=0.001), while in the female B27 positivity has higher prevalence of hip joint involvement (48.98% vs 32.43%, p=0.011). (4) From the aspect of age at onset, although the JoAS and AoAS group have similar B27 positive rate and gender ratio, JoAS group has obviously higher prevalence of peripheral symptom at onset (52.70% vs 24.00%), enthesitis (34.38%vs23.17%) and peripheral pattern (68.56% vs 42.07%), with all P value <0.001. Conclusions: HLA-B27 status, gender as well as age at disease onset are associated with the clinical manifestations of AS patients, which indicates the disease complexity and requires further attention in disease diagnosis. Larger scale studies and immunogenetic technology development are needed for better understanding of disease spectrum and mechanism. References: Ho, H. H., Chen, J. Y. Ankylosing spondylitis: Chinese perspective, clinical phenotypes, and associated extra-articular systemic features. Current rheumatology reports 2013;15:344 Chung, H. Y., Machado, P., van der Heijde, D., D'Agostino, M. A. & Dougados, M. HLA-B27 positive patients differ from HLA-B27 negative patients in clinical presentation and imaging: results from the DESIR cohort of patients with recent onset axial spondyloarthritis. Annals of the rheumatic diseases 2011;70: 1930–1936 O'Shea, F. D., Boyle, E., Riarh R. et al. Comparison of clinical and radiographic severity of juvenile-onset versus adult-onset ankylosing spondylitis. Annals of the rheumatic diseases 2009;68:1407–1412 Disclosure of Interest: None declared